Problems of poverty and political instability of Kyrgyzstan - Derid, Iryna (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
Practice shows that a number of countries rich in natural resources have failed to achieve sustainable economic development and a high level of welfare for the population. Researchers note that the availability of natural resources is often combined in countries with corruption, public opposition and the weakness of political institutions. The economies of countries that build on the export of natural resources are too dependent on world prices for these resources. The subject of the article is the problems of poverty and political instability of Kyrgyzstan as a country dependent on gold exports. The goal is to identify the main factors that lead to Kyrgyzstan’s economic backwardness, poverty and political instability in the presence of active resource exports. Objectives: to study the availability of gold and other natural resources in Kyrgyzstan, to analyze the country’s exports, to consider the level of living of the population, to identify the main problems of Kyrgyzstan development and to consider the prospects of overcoming them. General scientific methods are used: system analysis – to determine the peculiarities of the economy of Kyrgyzstan, the historical method – to demonstrate political instability in the country, statistical method – to demonstrate quantitative indicators. The following results were obtained:based on the study, the main factors leading to economic and political problems of Kyrgyzstan were identified. Conclusions: on a number of grounds, the country can be attributed to countries with a «resource curse»; in the gold mining industry mostly foreign companies are present, they are involved in social projects,but every fifth person in the country lives below the poverty line and therefore a significant proportion of the population are migrant workers abroad; there is constant political instability in the country and each new government is trying to make the most of the country’s gold reserves; the country will be able to get rid of the resource curse by implementing a number of recommendations for such countries, and especially by investing revenues from gold exports to in financial, physical and human capital; positive for solving the economic problems of Kyrgyzstan is its participation in the Eurasian Economic Union.